Inovasi Pelayanan Pembayaran Pajak Bumi dan Bangunan (PBB) di Badan Pengelolaan Keuangan dan Pajak Daerah (BPKPD) Pemerintah Kota Surabaya - Selavia, Exga Alma (Universitas 17 Agustus 1945 Surabaya, 2019)
The Surabaya city government has made innovations in land and building tax services in various matters such as the Standard Operating Procedures (SOP) for land and building tax services related to the payment of taxes, warnings and / or tax appeals, and so on. Standard Operating Procedures (SOP) that have been issued by the Regional Tax and Financial Management Agency (BPKPD) of the Surabaya city government for the Land and Building Tax (PBB) sector, namely payment and land and building tax (PBB) services through the Online System. Such as the payment of a Tax Return (SPPT), e-SPPT for the land and building tax (PBB), returning the name and / or correction of the address name that is not in accordance with the original, as well as the service letter (SK), and so on. From the PBB innovation online, the service process is more effective because it is based online and efficiently because it is free of charge which makes public service providers in this case especially the Regional Financial and Tax Management Agency (BPKPD) of Surabaya City run public services in accordance with the vision and mission of BPKPD those are transparent and accountable based on information technology. Then the negative impact caused, among others, is that there are still many people who do not know theonline PBB service most of the people only know a few services, such as the payment of the PBB using the land and building tax Mobile Car provided by the government, payment through M-Banking and so on. People who are blind to the existence of information technology that are very difficult with online PBB services do not rule out the possibility that there must be officers who are willing to help to operationalize technology.Keyword : Public service, service innovation, PBB online